FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI PISANG TALAS DI KECAMATAN HALONG KABUPATEN BALANGAN - Miranda Romaully; Juma Yanti (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
This study aimed to determine what factors influence the income of banana talas farmers. The location of the research was conducted in several villages namely Uren, Mamigang, Marajai and Binuang Santang where is central production of Talas banana in Halongs District Balangans Regency. Primary data collection through direct interviews to respondents of talas banana farmers that obtained 51 respondents. The multivariate variables that influenced income are age of farmer, level of education, number of family, number of tree and selling price of talas banana. The analysis used multiple regression with Cobb Douglass function. Based on the results that determinan coefficient (R square) is 0.617 mean that regression model of farmer income relatively good enough. The number of F statistik 14,496 with sig. 0,000 refered to accepted thus hypothesis which stated that variable of age, education level, number of family dependent, number of tree and selling price have simultaneously effect to talas banana farmer income. While significantly obtained t test result where number of family dependent, number of tree and selling price individually effect to farmer income. So the program of Balangan Regencey for increasing talas banana farmer income can conduct with concern for farmer with larger number of family dependent, with seedling grant of talas banana or extension land for talas banana planting, and secure for floor price of talas banana when large harvest happened.